Analyzing Errors Pattern in Mathematics Achievement among Senior Secondary School Students: A Case Study - Nwoke, Bright Ihechukwu; Duru, Darlington Chibueze; Ahanotu, Chioma; Ifediba, Chidiebere Precious (Journal of Instructional Mathematics, 2024)
Identifying student math errors is crucial as they hinder skill development in problem-solving, logic, and decision-making, given math's abstract nature. This study investigates mathematical errors among senior secondary school students in Owerri Municipal Council, Imo State. A descriptive survey research design was employed. The sample size comprised 150 senior secondary students in class three (SS3), randomly selected from five out of ten public senior secondary schools. It addressed three research questions and one null hypothesis tested. Data collection utilized two expert-validated instruments (Mock Mathematics Essay Score Sheet [MMESS] and the Mathematics Error Identification and Classification Checklist [MEICC]) with substantial reliability. The analysis involved frequency, percentage, and Chi-square methods. The findings revealed that the errors committed by students included conceptual errors, computational errors, defective algorithms, and wrong operational errors. Wrong operational errors were most common among male students, whereas female students were more prone to computational errors. A significant difference in the errors committed by male and female students was observed. Math teachers must address errors in class, engaging students to prevent recurrence. Findings suggest tailored interventions for diverse learning needs, highlighting gender-sensitive teaching. Future studies may explore long-term error trends and intervention efficacy.